A case of crossed cerebellar diaschisis on follow-up positron emission tomography/computed tomography with (18F) fluoro-D-glucose after treatment for glioblastoma - Priftakis, Dimitrios; Rondogianni, Phivi; Datseris, Ioannis (World Journal of Nuclear Medicine, 2019)
Crossed cerebellar diaschisis (CCD) represents the reduction of blood flow, metabolism, and oxygen consumption in the cerebellar hemisphere contralateral to a cerebral focal lesion. This phenomenon is the result of remote metabolic effects of cerebral lesions and it has been described since the first attempts for functional imaging of the brain, almost 40 years ago. Nevertheless, its clinical significance remains uncertain and new ways to use imaging of CCD for prognosis or assessment of novel therapies are being investigated. In this report, we present treatment for glioblastoma as a cause of CCD imaged on positron emission tomography/computed tomography with (18F) fluoro-D-glucose in our department.
Keywords: Crossed cerebellar diaschisis; fluoro-D-glucose; glioblastoma; positron emission tomography/computed tomography; stroke